Visual post-occupancy evaluation of a restorative garden using virtual reality photography: Restoration, emotions, and behavior in older and younger people - Boffi, Marco; Pola, Linda Grazia; Fermani, Elisabetta; Senes, Giulio; Inghilleri, Paolo; Piga, Barbara Ester Adele; Stancato, Gabriele; Fumagalli, Natalia (Frontiers in Psychology, 2022)
Natural environments have a restorative effect from mental/attentional fatigue, prevent stress, and help to revitalize psychological and physical resources. These benefits are crucial for promoting active ageing, which is particularly relevant given the phenomenon of population ageing in recent decades. To be considered restorative, green spaces have to meet specific requirements in ecological and psychological terms, that can be assessed through Post-Occupancy Evaluation (POE), a multimethod approach commonly used by environmental psychologists and landscape architects after construction to evaluate the design outcomes from the users' perspective. Generally, POEs consist of surveys and/or interviews accompanied by more or less structured observations of onsite users' behavior. Despite this, various practical constraints can prevent physical access to the renovated area (e.g., weather conditions, time/resources limits, health issues, bureaucratic constraints). Exploiting digital tools for such an assessment can be a crucial support in such circumstances. The current study presents the POE of a restorative garden for older adults in Milan, Italy. We developed a web application, that includes the exp-EIA© patented method, which allows participants to virtually explore a simulated environment and provide their feedback. We identified 3 representative viewpoints in the redeveloped garden differing from each other for the functions and the design principles that inspired the transformation. For each point of view we created 360° Virtual Reality photographs, that can be navigated by looking around, i.e. panning, from the standing point of each view. In connection to each virtual scene, a survey was conducted. The focus was the psychological experience related to each viewpoint in terms of restoration, emotions, and behavioral aspects, including the main activities prefigured by participants. The results of the virtual exploration show that the garden is perceived as restorative, with a more intense effect in a spot purposely designed. The emotions experienced in the garden are positive and a mild level of arousal is observed. The behavioral dimension is characterized by predominantly contemplative activities and contact with nature. A cartographic representation of the psychological and behavioral data is developed, to support the maintenance of the garden.